Tic Tac Toe Effectiveness in Teaching English Vocabulary for SD Dana Punia Singaraja Fifth Graders - NI Putu Ayu Niya Loviyani; Ni Nyoman Padmadewi; Luh Gde Rahayu Budiarta (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Vocabulary has become an essential element for students to communicate with others. This research intended to analyze students’ vocabulary mastery after being exposed to the Tic Tac Toe game as a learning medium. The total number of the class is 17 students of fifth-grade students of SD Dana Punia Singaraja in the 2021/2022 academic year. This research used quasi-experimental research in one group pre-test post-test design. The researcher took the accurate data during six meetings of implementation. Tic Tac Toe game used as a strategy with the familiar nine grid of Tic Tac Toe board. It used a vocabulary test with multiple-choice as an instrument. The vocabulary mastery was improved from 65.00 to 79.12 in the mean score. Besides, Kolmogorov-Smirnov and Levelene Statistic test results revealed that the test result was normally distributed and homogeny. Furthermore, the effect size was showing this game has a strong effect. As a result, Tic Tac Toe game had significantly affect students’ English vocabulary mastery.